EFEKTIVITAS PENGELOLAAN SAMPAH DI DINAS PERUMAHAN, KAWASAN PERMUKIMAN DAN LINGKUNGAN HIDUP KABUPATEN KUDUS - Rizka Hapsari, Armaviani; Kismartini, Kismartini; Zarkasyi Rahman, Amni (Journal of Public Policy and Management Review, 2024)
The waste problem in Kudus Regency continues to experience a significant increase in waste generation every year. Population growth, the rapid development of development, and the diversity of community activities are increasingly causing complex and complicated handling of waste management. The Kudus Regency Government also implemented a Zero Waste target in 2030, but this is contrary to the increase in annual waste generation in 2023 to 159,061.34 tons per year. The Kudus Regency Government then issued a waste management policy. The problem that arises is related to how effective the role of DPKPLH Kudus is in managing waste. The purpose of this research is to analyze the effectiveness of waste management in the Kudus Regency Housing, Settlement Areas, and Environment Office and identify inhibiting factors in waste management. This research uses descriptive qualitative research methods using the theory of Effectiveness according to Duncan. The results showed that waste management organized by the Housing, Settlement Areas and Environment Office of Kudus Regency has not been effective. The phenomenon of Goal Achievement, the purpose of waste management is to improve health and environmental quality and turn waste as a resource, but this goal has not been fully achieved in accordance with the waste management regulations. The time period sub-phenomenon has been running well and the target sub-phenomenon requires improvement. In the Integration phenomenon, the agency's ability to communicate with the community or other organizations cannot be said to be effective. In the procedure sub-phenomenon, waste management at DPKPLH is in accordance with the established SOP, while in the socialization process sub-phenomenon there are still problems that require improvement by the agency. The Adaptation phenomenon has been effectively implemented. In the sub-phenomenon of capacity building is carried out by conducting training, public discussion forums, monthly monitoring and evaluation; while in the sub-phenomenon of facilities and infrastructure in waste management organized by DPKPLH there are PDU facilities that are not operating optimally. This study also found problems that become inhibiting factors in waste management, this is related to not all people participating in waste management, a less massive and intensive socialization process, as well as limited budgets and human resources at PDU facilities, which are the cause of the unoptimality of PDU operations which should be able to reduce the amount of waste generation in Kudus Regency.